Exploitation Des Ressources Biologiques Et Dynamique De La Foret Classee De La Mekrou Au Benin - Bouko, Boni Sounon; Dossou, Paulin Jésutin; Amadou, Boureima; Sinsin, Brice (European Scientific Journal, ESJ, 2016)
The dynamics study of the preserved forest of Mekrou was discussed. The methodology used includes documentary research, Phytosociological surveys, diachronic analysis of satellite imagery, socio-economic surveys of different social and professional groups and the analysis and interpretation of data. It is obvious that in the area of the study, agriculture, animal husbandry, forestry and the use of medicinal plants are the main forms of natural resources exploitation. This operation, with population growth leads to a regressive evolution of plants and natural landscapes in favor of agricultural fields and fallow. The area of natural vegetation increased from 70, 53% in 1992 to 39,33% in 2012 in favor fields and fallow land increased from 17, 88% to 48, 77% in 2012. The numerical classification based on the presence-absence of vegetation species allowed us to individualize 6 vegetal communities. The Anogeissus leiocarpus, Khaya senegalensis and gallery forests group is the most diversified and most concentrated while Parkia biglobosa, Vitellaria paradoxa Field group is less diversified and less dense. The impact of soil occupation dynamics has resulted in the fragmentation of natural formations and reducing species diversity and density of ligneous.